2008
DOI: 10.1086/529142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pneumococcal Conjugate Polysaccharide and Free Polysaccharide Vaccines in Elderly Adults: Conjugate Vaccine Elicits Improved Antibacterial Immune Responses and Immunological Memory

Abstract: In adults, an initial dose of 7vPnC is likely to elicit higher and potentially more effective levels of antipneumococcal antibodies than is PPV. In contrast with PPV, for which the induction of hyporesponsiveness was observed when used as a priming dose, 7vPnC elicits an immunological state that permits subsequent administration of 7vPnC or PPV to maintain functional antipolysaccharide antibody levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
136
4
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(163 citation statements)
references
References 37 publications
13
136
4
10
Order By: Relevance
“…We have demonstrated that patients with COPD are able to mount immune responses comparable to those previously reported in healthy elderly patients (14,15). We showed that PCV7, when given at twice the dose recommended for children, induces a superior immune response to PPSV23 in COPD.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We have demonstrated that patients with COPD are able to mount immune responses comparable to those previously reported in healthy elderly patients (14,15). We showed that PCV7, when given at twice the dose recommended for children, induces a superior immune response to PPSV23 in COPD.…”
Section: Discussionsupporting
confidence: 76%
“…Bolded items represent a significant difference in absolute postvaccination IgG levels between vaccine groups and underlined items represent a significant difference in 1 month to baseline IgG ratio. levels in previously vaccinated healthy patients older than 70 years of age using the 1.0-ml PCV7 dose and by de Roux and coworkers who demonstrated the same results using the traditional pediatric dose (0.5 ml) in a vaccine-naive elderly population (14,15). Taken together, these studies suggest that although protein-conjugate vaccines may induce superior immune responses to the free polysaccharide vaccine, the optimal dose is uncertain and higher doses may be needed in those previously vaccinated with PPSV23.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In a study of patients with human immunodeficiency virus, the immune response was better for patients vaccinated according to this strategy than in those vaccinated with only a dose of PPV (40). Similar results were found in a population of elderly adults (41). Studies evaluating this prime-boost strategy in RA patients are needed.…”
Section: Discussionmentioning
confidence: 61%
“…9 Some immunological studies 10 have suggested improved immunogenicity of PCV7 over PPV23 in adults and/or the elderly. [11][12][13][14][15] while others have reported no significant differences. 10,[16][17][18][19] In 2014 the first large clinical trial of PCV13 in the adults aged >65 y (CAPiTA trial -Community Acquired Pneumonia Immunization Trial in Adults 20 ) was completed.…”
Section: Introductionmentioning
confidence: 92%